KNOWLEDGE MANAGEMENT INITIATIVES, INNOVATION AND GLC PERFORMANCE (Journal of Information and Communication Technology, 2009)
A model of knowledge management initiatives, innovation and performance evaluation was developed and tested on listed Malaysian Government-Linked companies (GLC). Data collected from 273 employees representing the three different levels of management were subjected to structural equation modeling analysis. The proposed model fits the data well. Results indicate that employees perceived knowledge management initiatives as important antecedents of innovation in the GLC, and innovation in return resulted in better organizational performance.